2015
DOI: 10.1186/s12981-015-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 protease inhibitor drug resistance in Kenyan antiretroviral treatment-naive and -experienced injection drug users and non-drug users

Abstract: BackgroundAlthough injection drug use drives antiretroviral drug resistance, the prevalence of protease inhibitor (PI) resistance among Kenyan IDUs remains undetermined. We, therefore, explored PI resistance mutations and their association with viral load and CD4+ T cell counts in HIV-1 infected IDUs (ART-naive, n = 32; and -experienced, n = 47) and non-drug users (ART-naive, n = 21; and -experienced, n = 32) naive for PI treatment from coastal Kenya.ResultsOnly IDUs harboured major PI resistance mutations con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
(41 reference statements)
0
6
1
Order By: Relevance
“…We found a similar PDR prevalence (9%-13%) across urban and rural sites, which was contrary to our expectation that PDR 1) 20 (0) 14 (118-24 39 7) 32 (7) 7 (025 -35 247 (30) 169 (24) 78 635-50 386 (27) 218 (18) 168 950+ 143 (13) 80 6 prevalence would be lower at the rural than the urban clinics. Whereas some previous studies have generally found lower PDR in rural settings [39][40][41][42][43][44][45][46][47][48][49], our more recent results may reflect improved access to ART in the rural regions. Our observed 12% PDR prevalence among 212 adult participants (11% among ARV-naive) at the rural Maseno clinic was slightly higher than the 9% TDR prevalence observed in another recently published study of 87 ARV-naive participants conducted in 2012, also based in Western Kenya [50], providing further evidence of PDR in this rural setting.…”
Section: Discussioncontrasting
confidence: 78%
“…We found a similar PDR prevalence (9%-13%) across urban and rural sites, which was contrary to our expectation that PDR 1) 20 (0) 14 (118-24 39 7) 32 (7) 7 (025 -35 247 (30) 169 (24) 78 635-50 386 (27) 218 (18) 168 950+ 143 (13) 80 6 prevalence would be lower at the rural than the urban clinics. Whereas some previous studies have generally found lower PDR in rural settings [39][40][41][42][43][44][45][46][47][48][49], our more recent results may reflect improved access to ART in the rural regions. Our observed 12% PDR prevalence among 212 adult participants (11% among ARV-naive) at the rural Maseno clinic was slightly higher than the 9% TDR prevalence observed in another recently published study of 87 ARV-naive participants conducted in 2012, also based in Western Kenya [50], providing further evidence of PDR in this rural setting.…”
Section: Discussioncontrasting
confidence: 78%
“…Past studies in Kenya have identified mutations conferring resistance to specific classes of ARVs [ 9 - 11 ]. At the coastal region of Kenya, L90M, M46I and D30N mutations conferring resistance to PIs were identified among out-patients injecting drug users [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies in Kenya have identified mutations conferring resistance to specific classes of ARVs [ 9 - 11 ]. At the coastal region of Kenya, L90M, M46I and D30N mutations conferring resistance to PIs were identified among out-patients injecting drug users [ 9 ]. A study on HIV-1 drug-resistance patterns in Nairobi identified M184V, K65R, T215Y and K70R mutations conferring resistance to NRTIs and K103N, G190A, V106A, Y184V, A98G, Y181C mutations conferring resistance to NNRTIs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, over 50,000 ISUs have been identified, and the number is on the increase predominantly in coastal, urban sites, peri-urban areas and cities ( 6 ). The prevalence of HIV infection in Kenyan ISUs is ∼18.3% with higher incidence of 18.7% mainly at the coast linked to high rates of injection substance use ( 7 ). Previous studies have reported TB to be the common co-infection in Kenyan HIV infected ISUs ( 8 ).…”
Section: Introductionmentioning
confidence: 99%